Parkinson's Disease cost studies in Brazil: an evident scientific gap (Research, Society and Development, 2021)
The financial impact of Parkinson's Disease on society has been widely discussed in recent decades and is expected to increase in the future, along with an aging population. However, the scarcity of studies on the cost of the disease in Brazil makes it difficult to carry out forecasts and calculations of future estimates, impairing the assessment of the economic impact on the individual's life and on health systems, both public and private. The objective of this research is to verify whether the scarcity of studies of this nature in Brazil is a reality, through a research of cost studies with the treatment of Parkinson's Disease carried out in recent years. A systematic literature review, based on a search for keywords on the topic, identified 27 articles that met the inclusion criteria and refinement filters applied to the initial portfolio. Of these, only two studies were carried out in Brazil (an original article and a systematic review), which proves the lack of studies on the subject in the country.